Beyond Smiles: Static Expressions in Maxillary Protrusion and Associated Positivity - Chen, Lijing; Jiang, Jiuhui; Li, Xingshan; Ding, Jinfeng; Paterson, Kevin B.; Rao, Li-Lin (Frontiers in Psychology, 2021)
Smiles play an important role in social perception. However, it is unclear whether a similar role is played by static facial features associated with smiles (e.g., stretched mouth, visible teeth). In dental science, maxillary dental protrusions increase the baring of the teeth and thus produce partial facial features of a smile even when the individual is not choosing to smile, whereas mandibular dental protrusions do not. We conducted three experiments to assess whether individuals ascribe positive evaluations to these facial features, which are not genuine emotional expressions. In Experiment 1, participants viewed facial photographs of maxillary and mandibular protrusions and indicated the smiling and emotional status of the faces. The results showed that, while no difference was observed in perception of the presence of a smile across both types of dental protrusion, participants felt more positive to faces with maxillary than mandibular protrusions. In Experiment 2, participants completed an IAT test measuring implicit attitudes towards faces with maxillary versus mandibular protrusions. Results showed that participants had more positive attitude toward faces with maxillary than mandibular protrusions. In Experiment 3, individuals with either maxillary or mandibular protrusions completed the same IAT test to assess whether any preference would be affected by in-group/out-group preferences. The results showed both groups had more positive attitudes toward faces with maxillary protrusion, indicating that this preference is independent of the group effect. The findings suggest that facial features associated with smiles are viewed positively in social situations. We discuss this in terms of the social-function account.